The poly(A)-limiting element is a conserved cis-acting sequence that regulates poly(A) tail length on nuclear pre-mRNAs - Gu, Haidong (The National Academy of Sciences, 1999)
Most vertebrate mRNAs exit the nucleus with a 200+-residue poly(A) tail and are deadenylated to yield heterogeneous polymers of 50–200 adenosine residues on any given mRNA. We previously reported that Xenopus albumin mRNA and pre-mRNA have an unusually short, discrete 17-residue poly(A) tail and showed that regulation of poly(A) length is controlled independently by two cis-acting poly(A)-limiting elements (PLE A and PLE B) located in the terminal exon. The present study sought to determine the generality of this regulatory mechanism. Transferrin mRNA also has a discrete <20-nt poly(A) tail, and deletion mapping experiments identified an element homologous to the albumin gene PLE B within the terminal exon of the transferrin gene that conferred poly(A) length regulation on a globin reporter mRNA. Based on this similarity the PLE B sequence was used in a database search to identify candidate mRNA targets for regulated polyadenylation. Of the several hundred sequences identified in this manner we focused on HIV-EP2/Schnurri-2, a member of a family of genes encoding related zinc finger transcription factors. A striking feature of the PLE-like element in these genes is its location 10–33 bp upstream of the translation stop codon. We demonstrate that HIV-EP2 mRNA has a <20-nt poly(A) tail, for which the identified PLE-like sequence is responsible. These results indicate that the presence of a PLE can predict mRNAs with <20-nt poly(A) tails, and that nuclear regulation of poly(A) tail length is a feature of many mRNAs.